KEMAMPUAN MENULIS SURAT DINAS SISWA KELAS VIII MTs NURUL IKHSAN SUNGAI RAWA KECAMATAN SUNGAI APIT KABUPATEN SIAK - Desi Saputriyani; Nur Mustafa; Nursal Hakim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research discusses the ability to write letters to the 8th grade students MTs Nurul Ikhsan Sungai Rawa Kecamatan Sungai Apit subdistrict siak district. This research aimed to describe the parts of the letter of service consisting of the letter head letter, date letter, number letter, attachment, terms, mail destination address, greetings, contentof letter, closing, name and signature, and a copy. The method used is descriptive method with qualitative approach. Sources of data in this study are the students of grade 8th MTs Nurul Ikhsan Sungai Rawa Sungai Apit subdistrict Siak district. This research data is all student of 8th grade MTs Nurul Ikhsan Sungai Rawa Sungai Apit consisting of 1 class amounted to 36 students. This result of this study is seen from the result of the ability to writer writing skills of the 8th grade students of MTs Nurul Ikhsan Sungai Rawa. The ability to writer letters of the 8th grade students of MTs Nurul Ikhsan Sungai Rawa Sungai Apit district siak district, recapitulation of official letter writing is low ability with average value 67,9%.Keyword : Writing Ability, Letter of Official, and part of the official letter.